Problematics of Transanal Evisceration - Boris, HrbatÃƒÂ½ (Journal of Medical Biomedical and Applied Sciences, 2017)
Authors of this paper deal with rare surgical entity named transanal eviscerationâ. This term isâ horribleâ and its clinical picture and view itself even worse. Meeting this condition in clinical practice brings aÂ challenge for the attending surgical staffÂ  to quickly commence with the proper management of arised situation. Even been so rare (evisceration) to be met in everyday practice, the authors think, that aÂ knowledge about the possibility of existence of this disastrous condition, could be helpfull for emergent surgical wards. The authors give aÂ short review of this topic and present aÂ personal experience with this clinical entity.